Akibat Hukum Terhadap Bank Atas Pembatalan Hak Tanggungan Melalui Putusan Pengadilan Berkekuatan Hukum Tetap - Ryan Dwitama Hutadjulu; Lastuti Abubakar; Tri Handayani (Jurnal USM Law Review)
The research was conducted to analyze the legal impact on the position and obligations of the bank as the holder of mortgage rights (HT) for HT which has been determined to have no legal force by a court decision. With regard to lending, the existence of guarantees is a matter of sufficient concern to banks. Until now, land has been highly favored by banks as collateral for loans with mortgage rights. Cancellation of land ownership certificates can be submitted for land that has become HT. By canceling the mortgage right, the bank will lose the guarantee for the credit that has been issued, especially if the debtor is in bad credit status. Normative juridical is the method been used in this research. It is concluded from the discussion result that the legal consequences of the mortgage rights that have been determined to be non-forceable by a court decision on the position and obligations of the bank as the mortgage holder is that the bank will lose its position as preferred creditor. The cancellation of the agreement on the transfer of land rights also causes the cancellation of the mortgage agreement, considering that the object of the agreement does not meet the legal requirements of the agreement. The contractual relationship between the debtor and the bank as the creditor in the said rights agreement is considered non-existent and must be returned to its original state before the mortgage agreement.